The process of holism: a critical analysis to bridge the gap between sustainable architecture design principles and elements defining Art of Sustainability. (3rd April 2017) - Farid, Ayman A.; Zagloul, Weaam M.; Dewidar, Khaled M.
ABSTRACT: In 2004, Jason F. McLennan, in his book, The Philosophy of Sustainable Design, stated that 'Sustainable design is the philosophy that simply asks, what is the most we can do on a given project to enhance the quality of the built environment ' or 'it is a design philosophy that seeks to maximize the quality of the built environment, while minimizing or eliminating negative impact to the natural environment'. Such philosophy is a simple translation to 'Sustainable Design' in terms of 'Sustainable Development'. In 2013, in SudBE international conference held in China, our research team coined the term 'Art of Sustainability' as the key element for sustainable design development. It links the concept of sustainable development to sustainable design principles. The aim of this research work is to establish a new model that links the six major sustainable design principles ( The respect for: 1 – The wisdom of natural systems, 2 – The human vitality principle, 3 – The ecosystem principle, 4 – Cycle of life 5 – Energy and natural resources, and 6 – And finally the process – Holistic thinking principle ) to the elements defining the Art of Sustainability which are: ( 1 – The meaning of space, 2 – The innovative structures, 3 – The innovation in construction and building material, and 4 – The contextual and cultural values ). Such model can define the state of paradigm shift in sustainable design in architecture, where sustainable design seeks better building performance in terms of sustainability while Art of Sustainable design model would seek a better sustainable design performance, which is a step forward towards more sustainable practice.